Impact of Frontliner Quality, Digital Services, and Office Facilities on Taxpayer Satisfaction - Prihastuti, Andi Wiwiek; Hamzah, Muhammad Nasir; Rosanti , Novita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to understand and analyze the direct and indirect effects of Frontliner Quality, Digital Service Quality, and Office Facilities on Taxpayer Compliance and Satisfaction as intervening variables at the SAMSAT Makassar Office.The analysis method used is Path Analysis with SmartPLS, aimed at depicting the actual state of the research object to understand the effects of Frontliner Quality, Digital Service Quality, and Office Facilities on Taxpayer Compliance and Satisfaction as intervening variables at SAMSAT Makassar by submitting statements through questionnaire to 100 active motor vehicle taxpayers.The research findings are  (1) Frontliner Quality has a positive but insignificant effect on taxpayer satisfaction at SAMSAT Makassar. (2) Digital service quality has a positive and significant effect on taxpayer satisfaction at SAMSAT Makassar. (3) Office facilities have a positive and significant effect on taxpayer satisfaction at SAMSAT Makassar. (4) Frontliner Quality has a positive but insignificant effect on taxpayer compliance at SAMSAT Makassar. (5) Digital service quality has a positive and significant effect on taxpayer compliance at SAMSAT Makassar. (6) Office facilities have a positive but insignificant effect on taxpayer compliance at SAMSAT Makassar. (7) Satisfaction has a positive and significant effect on taxpayer compliance at SAMSAT Makassar. (8) Frontliner Quality has a positive but insignificant effect on compliance through taxpayer satisfaction at SAMSAT Makassar. (9) Digital service quality has a positive and significant effect on compliance through taxpayer satisfaction at SAMSAT Makassar. (10) Facilities have a significant effect on compliance through taxpayer satisfaction at SAMSAT Makassar.